Investigação farmacoepidemiológica do uso do clonazepam no distrito sanitário leste em Natal-RN - Diniz, Rodrigo dos Santos (2011)
Prescription errors are the most serious type of medication errors found in the health system. The main purpose of this study was to evaluate the quality of clonazepam prescriptions. A descriptive and observational study with retrospective data collection was conducted at 30 community pharmacies in Natal/RN, Brazil, after informed consent was obtained from the pharmacists. A sample of 313 prescription notifications was randomly collected in October 2009. They were analyzed for legible handwriting and completeness. During the study, one researcher, two pharmacists, and one pharmacy undergraduate student evaluated patient and purchaser identification, pharmaceutical form, dosing regimen, administration route, and prescription by generic name. This research was approved by the institutional Ethics Committee. Among the 313 collected notifications, only 44.1% were legible. A total of 55.91% (175/313) had at least one illegible item, 100% contained incomplete information, and 97.12% (304/313) contained one or more abbreviations. The proportion of illegible handwriting related to the patient s identification (p=0.0001) was statistically significantly greater than that related to the drug purchaser s identification (p=0.0004). Contrary to legal requirements, prescriptions with the generic name accounted for 13.42% (42/313) of the total. All the examined notifications were handwritten. Prescription errors, which potentially can have serious consequences, have been evaluated worldwide, although little is known about this subject as it relates to community pharmacies. This study showed high percentages of prescribing problems, which justifies the development of future research about medication errors in community pharmacies and education activities for prescribers